Analisis Pengaruh Tingkat Pendidikan Terhadap Kesejahteraan Masyarakat Menggunakan Indikator Badan Kependudukan dan Keluarga Berencana Nasional - Eha, Jufrin La (Journal of Geographical Sciences and Education, 2024)
Education is one of the main keys to the welfare of families and society. Through education, the social status of a society can changes in terms of economic aspects and other aspects of life within a family. The research aims to determine the effect of education level on community welfare. The method used is a literature study. The research results show that the majority (90%) of the review results show a positive correlation between education and community welfare. However, several other factors are thought to influence the level of welfare, so it is necessary to carry out in-depth examination of the relationship between the level of education and community welfare from different variables. This study can illustrate that education is a long-term investment that influences social change in society.